Value of combined XCT/SPECT technology for avoiding false positive planar 123I-MIBG scintigraphy - Özer, S.; Dobrozemsky, G.; Kienast, O.; Beheshti, M.; Becherer, A.; Niederle, B.; Kainberger, F.; Dudczak, R.; Kurtaran, A. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: The clinical value of combined XCT/SPECT technology in a single device in patients undergoing 123I-MIBG scintigraphy was analyzed. Methods: 31 patients (19 men, 12 women; mean age 55 years, range: 31-79 years) demonstrating focal accumulation in planar 123I-MIBG scan were further investigated with a double headed gamma camera with an X-ray tomograph mounted on the same gantry (GE Medical Systems, Millennium VG with Hawkeye, Milwaukee, USA) for anatomical definition of the focal 123I-MIBG uptake. The patients were referred to 123I-MIBG scintigraphy because of biochemically (81%) and/or clinically (19%) suspected pheochromocytoma. Results: In 23 out of 31 patients (74%) the fused images demonstrated physiological accumulation (i. e. intestinal, renal) of 123I-MIBG. In two patients (6%) suspected adrenal MIBG-accumulation was caused by inhomogeneous liver uptake. In two patients (6%) focal abdominal accumulation was correctly localised in the adrenal glands. Furthermore, the differentiation of bone metastasis from a local recurrence for phaeochromocytoma was accurately possible for two patients (6%). Adrenal lesions mimicking liver foci were correctly localised in the remaining two patients (6%). Conclusion: Our study demonstrates the clinical value of XCT/SPECT in a single device in patients demonstrating focal 123I-MIBG uptake in planar scintigraphy. The combined XCT/SPECT technology provides a higher diagnostic accuracy.
Keywords: Phaeochromocytoma; MIBG scintigraphy; XCT/SPECT; image fusion